Correction to: Effect of Resistance and Endurance Trainings on Nrf2/Keap1 Signaling Pathway in Testicular Tissue of Type 2 Diabetic Rats - Zahra Nadi; Yusef Abbasi; Farideh Jalali Mashayekhi; Mohammad Bayat; Parvindokht Bayat; Maryam Baazm (Journal of Mazandaran University of Medical Sciences, 2023)
Correction to: Effect of Resistance and Endurance Trainings on Nrf2/Keap1 Signaling Pathway in Testicular Tissue of Type 2 Diabetic Rats